PEMALSUAN IDENTITAS ANAK DALAM AKTA OTENTIK OLEH KELUARGA KORBAN AKIBAT PEMERKOSAAN - Nurul Fakhriyah; Ahmad Mahyani (Gapenas Publisher, 2022)
The purpose of this study is to find out how the state guarantees rape child status, that no one wants to be the victim of one's vile act, the result of rape is not uncommon in trauma, pregnancy. The birth of a child must have been a heavy responsibility for the victim to assume a new status as a mother of an unwanted child. Everyone is protected and granted rights by the state from the womb until it recovers age. While a rape victim is allowed to have an abortion, it is not uncommon for a victim to keep her pregnancy in check until the child resulting from rape is born in the world. The birth of the child is certainly born as well as the rights of the child, the parental obligation to give to the identity of the child which is guaranteed by the state should be highly valued and respected to protect the dignity and dignity of the child as it is defined by the legislation on child protection, when the rights of the child are taken away by the family as a result of rape, there isa conflict between the rules and the fact that the child has lost his identity as a result of the selfishness of the party. The child has a right to have an identity on him since he was born in the world. The child in general from the rape right to know his or her identity starting with his or her biological parents, usually hidden in order to cover up the shame of the rape victim's family. This would surely be fateful for the present and future because authentic deeds are the letters used for human life. It is ignored by the victims' families, whereas it is a violation of the penal penal code on the part of authentic deed forgery as long as the maximum prison penalty of six years is threatened, and it is charged with 2016's second amendment act on child protection